2017
DOI: 10.1111/1471-0528.14712
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety, and acceptability of first‐trimester medical termination of pregnancy performed by non‐doctor providers: a systematic review

Abstract: BackgroundPrevious systematic reviews have concluded that medical termination of pregnancy (TOP) performed by non‐doctor providers may be as effective and safe as when provided by doctors. Medical treatment of incomplete miscarriage by non‐doctor providers and the treated women's acceptance of non‐doctor providers of TOP has not previously been reviewed.ObjectivesTo review the effectiveness, safety, and acceptability of first‐trimester medical TOP, including medical treatment for incomplete miscarriage, by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
2
21
0
2
Order By: Relevance
“…This is true in both low‐ and high‐income settings and where the ultrasound dating of gestational age is part of the protocol. This approach has been found to be well accepted and cost‐effective in the high‐income setting of Sweden …”
Section: Evolution Of Mtop Regimensmentioning
confidence: 99%
See 2 more Smart Citations
“…This is true in both low‐ and high‐income settings and where the ultrasound dating of gestational age is part of the protocol. This approach has been found to be well accepted and cost‐effective in the high‐income setting of Sweden …”
Section: Evolution Of Mtop Regimensmentioning
confidence: 99%
“…A recent systematic review showed that MTOP provided by trained non-doctors healthcare providers is as effective and as acceptable to women when compared with that provided by doctors. 33 Therefore, in countries where there is a shortage of medical staff, the MTOP service can be provided by trained midlevel non-doctors, thus making safe TOP more accessible to women. This is true in both lowand high-income settings and where the ultrasound dating of gestational age is part of the protocol.…”
Section: Evolution Of Mtop Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsafe abortion results in preventable morbidity and mortality; in women of childbearing age 22,800 deaths worldwide are estimated to occur annually [ 1 ]. An important reproductive health service, medical termination of pregnancy (MToP) is an acceptable and safe option for women seeking abortion in the first and second trimesters of pregnancy [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…WHO guidelines recommend that they can be provided at primary care level and by non-physician providers. Specialised investigations are not needed and the process can be managed outside of a facility and without the direct supervision of the provider 8–15. Service delivery with limited medical supervision can improve privacy, convenience and acceptability of the abortion process without compromising safety and effectiveness.…”
mentioning
confidence: 99%